Tradizione orale a Resia - Dapit, Roberto (Traditiones (Ljubljana), 1999)
Based on his research work the author tries to established the present situation of oral tradition in Resia, comparing it with the extremely rich material which has been recorded by Milko Matičetov in Resia since 1962. Despite numerous economic, social and cultural changes Resia remains a privileged territory in which the roots of folk culture are still firm. This is further proved by the new material in the Resian language described in this article which has already been researched by Dr. Milko Matičetov.
Keywords: Italia; mitologija; mythology; ljudsko izročilo; ustno izročilo; ethnology; etnologija; Resia, Friuli; Rezija; Slovenci; Slovenes